Acute Care Utilization and Health Care Expenditures in Medicaid‐Enrolled Children. Issue 1 (January 2022) - Masonbrink, Abbey R.; Richardson, Troy; Goyal, Monika K.; Hall, Matt; Reed, Jennifer L.; Alpern, Elizabeth R.; Samuels-Kalow, Margaret E.; Neuman, Mark I.
Abstract : Objectives: Although recent health care reform efforts have focused on minimizing high cost health care utilization, the relationship between acute care use and health care expenditures among certain vulnerable populations such as Medicaid-insured children remains poorly understood. We sought to evaluate the association between acute care utilization and health care expenditures and to identify characteristics associated with high spending. Methods: We performed a retrospective cohort study of Medicaid-enrolled children 1–21 years old from 1/1/2016 to 12/31/2016. Children were categorized by acute care use (including emergency department and urgent care visits) as 0, 1, 2, 3, and 4 or more visits. Our main outcomes were annualized spending, total per-member-per-year spending, and acute care-related per-member-per-year spending. Results: There were 5.1 million Medicaid-enrolled children that comprised the study cohort, accounting for US 32.6 billion in total spending. Children with 4 or more acute care visits were more likely to be younger than 2 years or older than 14 years, female, and have a chronic condition. Children with 4 or more acute care visits consisted of only 4% of the cohort but accounted for 15% (US 4.7 billion) of the total spending. Increasing acute care visits were associated with increasing total annualized spending in adjusted analyses ( P < 0.001). This association was disproportionately observed in older age groups and children without chronic medical conditions. Conclusions: Medicaid spending for children increases with increasing acute care use; this trend was disproportionately observed in older age groups and children without chronic medical conditions. Improved understanding of factors contributing to frequent acute care utilization and disproportionate spending is needed to potentially reduce unnecessary health care costs in these pediatric populations.